Identification of hydrothermal alteration minerals applying hyperspectral methods to multispectral images - Chacón Abad, Néstor (2017)
Advance spaceborne thermal emission and reflection radiometer (aster) is the first sensor with multi band observation in thermal infrared region (8-12 micrometers) with 90 meters of spatial resolution and 5 spectral bands specially designed to discriminate rocks from earth crust. Different process were applied in order to discriminate alteration minerals and rock groups by using not only the thermal infrared band but also the visible and near infrared bands.The area of study is located is situated in the Department of Cuzco in the southern portion of the Peru Tertiary Volcanic Belt and located 170 kilometres northwest of Arequipa. The area lies within the Peruvian altiplano at an altitude of 4,470 to 5,370 metres. The availability of multispectral data from the satellite- borne ASTER (advance Spaceborne Thermal emission Reflection Radiometer) instrument has provided and increased potential for mapping hydrothermal alteration systems.The ASTER instrument has six bands in the Swir region strategically positioned to map distinctive absorption features of alteration minerals with Al- OH and Mg-OH bonds. That permits to interact with the Terra Spec.